Effects of daily porcine somatotropin administration on tile performance and carcass characteristics of finishing swine - Fitzner, G.E.; Nichols, David A.; Schricker, B.R.; Darden, D.E.; Weeden, T.L.; Goodband, Robert D.; Hines, Robert H.; Nelssen, Jim L.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-four pigs (72 barrows and 72 gilts) were utilized in six treatments with six pens each to evaluate four levels of daily porcine somatotropin (pST) injections (0, 1, 3, or 5 mg/d) in combination with diets containing 13 or 16% crude protein (CP). One randomly selected pig from each pen was slaughtered when it reached a weight between 230 and 240 lb. Daily feed intake (ADFI), tenth rib backfat, and estimated percentage of lean pork were reduced in pigs fed the 13% CP diet and injected with 3 mg/d pST compared to pigs fed the same diet and injected daily with a placebo. Feed intake was reduced in pigs fed the 16% CP diet and injected daily with 3 and 5 mg/d pST. Improvement in feed conversion (F/G), tenth rib backfat, and estimated percentage lean pork occurred when pigs fed the 16% CP diet were injected with 1 mg/d, with greater improvements occurring at the 3 and 5 mg/d levels of pST. The improvement in F/G and the greater magnitude of response observed in pigs fed 16% CP diets compared to the response of pigs fed the 13% CP diet indicate that both the performance and carcass characteristics of pigs injected with pST are dependent on the dietary CP content.
Keywords: Swine; Porcine somatotropin; Finishing pigs; Crude protein